2017
DOI: 10.1891/0730-0832.36.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Psychological Distress and Mother–Infant Relationship: Multiple-Birth Versus Singleton Preterm Infants

Abstract: Mothers of multiples had greater PTS symptoms at baseline, anxiety at discharge, and depressive symptoms at six months than mothers of singletons. Mothers of multiples also had more positive home environments at six months. Multiple birth was a risk factor for psychological distress but not for less positive mother-infant interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…In addition, they also reported emotional stress more frequently compared with term group parents. Similar experiences have been reported in earlier studies [ 2 , 3 ], especially in cases where the preterm infant was admitted to the ICU [ 5 ]. In our study, parents with term infants expressed positive emotions more frequently than did those in the preterm group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, they also reported emotional stress more frequently compared with term group parents. Similar experiences have been reported in earlier studies [ 2 , 3 ], especially in cases where the preterm infant was admitted to the ICU [ 5 ]. In our study, parents with term infants expressed positive emotions more frequently than did those in the preterm group.…”
Section: Discussionsupporting
confidence: 87%
“…These are more prominent for parents of preterm infants than for parents of term infants [ 2 ]. An assessment of maternal psychological distress in singleton versus multiple-birth preterm infants found that mothers with multiple births had greater posttraumatic stress symptoms, anxiety at discharge, and depressive symptoms at 6 months as compared to mothers of singletons [ 3 ]. In a follow-up clinic evaluation of parents and their preterm infants, many reported parental concerns about medical and developmental outcomes that were unsupported by their child’s diagnosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Manual backward elimination was used to select the final model, with significance level for retaining the covariates in the final model set at .1. The multiple birth, intervention, and study site variables were considered in model selection process as possible controls, because they had shown effects in previous analyses (Gondwe, Yang, White‐Traut, & Holditch‐Davis, ; Holditch‐Davis et al, ). Analyses were performed using Statistical Analysis Software (SAS) version 9.3.…”
Section: Methodsmentioning
confidence: 99%
“…The slope of fetal growth in twin pregnancies is lower than that in a singleton pregnancy, and LBW is known to be a complication in 50% of twin pregnancy cases [ 21 ]. Neonates born from multiple pregnancies undergo many socioeconomic, educational, and emotional problems [ 22 , 23 ]. Therefore, since the impact on future healthcare could differ between singleton and multiple pregnancies when the effects of LBW on healthcare are considered, it might be better to exclude multiple pregnancy cases from such analyses.…”
Section: Discussionmentioning
confidence: 99%